O efeito do ultra-som em reações químicas - Martines, Marco Antonio Utrera [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci Júnior, Miguel [UNESP] (Sociedade Brasileira de Química, 2000)
Unusual chemical phenomenon associated with ultrasound is on account of cavitation effect. The ultrasound increase the rate and yield of chemical reaction on account of its ability to emulsify liquids. When the ultrasound is used in metallic catalyst reaction the activity of catalyst is increased because the ultrasound clean the surface of catalyst. Sonogels have a fine porosity and large specific surface improving different properties. This paper deals with ultrasound phenomenon and gives some examples of reactions and properties where this radiation takes an important role.
The ultrasound effect on chemistry reactions
Keywords: ultrasound; sonochemistry; sonoluminescence; sonogel